Pengaruh Corporate Social Responsibility dan Asimetri Informasi terhadap Kinerja Keuangan pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Periode 2021–2024 - Salsabila Yara Ramadhani; Sudrajat Sudrajat (AKUNTANSI 45, 2026)
This study investigates the influence of Corporate Social Responsibility (CSR) reporting and information asymmetry on the financial performance of mining firms listed on the Indonesia Stock Exchange (IDX) spanning the period 2021 to 2024. Adopting a quantitative approach, the study utilizes secondary data sources, including annual reports, sustainability disclosures, and stock market summaries. By applying a judgment-based sampling technique, a total of 32 entities were selected, yielding 128 observations. Panel data regression estimation was executed via Stata 19, wherein the Common Effect Model (CEM) was determined as the most appropriate fit based on the Chow and Lagrange Multiplier tests. To mitigate violations concerning heteroskedasticity and autocorrelation assumptions, the analysis incorporated a robust cluster standard error method. The empirical findings demonstrate that CSR disclosure exerts a significant positive impact on corporate financial performance. Concurrently, information asymmetry does not negatively affect financial performance. This finding highlights the distinctive nature of the extractive sector, where elevated information complexity aligns with robust financial performance propelled by commodity price dynamics. Ultimately, these insights provide a strategic framework for corporations to design sustainability initiatives and data transparency to strengthen stakeholder confidence.